NUSYUZ DALAM SUAMI ISTRI PERSPEKTIF AL-QUR’AN DAN HADIS - Multazam, Umar (LPPM STAI Muhammadiyah Probolinggo, 2024)
This article aims to understand the concept of nusyuz in husband and wife from the perspective of the Koran and Hadith. One of the family law topics covered in the Qur'an and hadith is the problem of nusyuz. Living together as a couple in a marriage relationship actually has positive and negative effects. The establishment of a comfortable, peaceful and lasting environment for both is a positive consequence, marital conflict often results in quarrels, heated discussions, and sometimes even physical and psychological violence, which can disrupt the harmony of husband and wife relationships and give rise to what is generally known as nusyuz. However, negative consequences also cause disharmony in marriage. Nusyuz can occur for a number of reasons, such as one party's entitlement to another, or dissatisfaction with how their partner is treated. This can also occur as a result of the husband's mistake in defending his wife. The problems that arise in nusyuz include stinginess and jealousy. To answer and conclude this nusyuz problem, this research uses qualitative methods by collecting data from library sources. The analysis was carried out using the content analysis method, which was then used to conclude the research findings. Keywords: Nusyuz; Husband and wife; Marital conflict.